Synthesis, characterization and antitumor activity of polymeric copper(II) complexes with thiosemicarbazones of 3-methyl-5-oxo-1-phenyl-3-pyrazolin-4-carboxaldehyde and 5-oxo-3-phenyl-3-pyrazolin-4-carboxaldehyde - Leovac, Vukadin M.; Bogdanovic, Goran A.; Jovanovic, Ljiljana S.; Joksovic, Ljubinka; Markovic, Violeta; Joksovic, Milan D.; Dencic, Sonja Misirlic; Isakovic, Andelka; Markovic, Ivanka; Heinemann, Frank Wilhelm; Trifunovic, Srecko; Dalovic, Ivica (Journal of Inorganic Biochemistry, 2011)
New polymeric copper(II) complexes with two tridentate ONS thiosemicarbazone ligands containing substituted pyrazolone moiety were synthesized and characterized by means of spectroscopic, electrochemical and crystallographic techniques. While both ligands exist as different tautomers in the solid state and DMSO-d(6) solution, Cu(II) ion coordinates the ligands from the same tautomeric form with square-pyramidal geometry around each Cu atom. In the crystal structures, the copper(II) complex cation forms polymeric chains [Cu(L)Cl(+)](n) with a bridging chlorine atom. One of the complexes was found to have a significantly higher cytotoxic potential in comparison with cisplatin in inhibition of several cell lines (HL60, REH, C6, L929 and B16). The results obtained on the basis of flow cytometry indicated that apoptosis could be possible mechanism of cell death. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Copper(II) complexes; Pyrazolone; Thiosemicarbazone; X-ray structures; Electrochemistry; Cytotoxicity